Cellular and Molecular Tissue Response to Triple Antibiotic Intracanal Dressing - Swerts Pereira, Maristela Soares [UNESP]; Rossi, Marcos A.; Cardoso, Cristina Ribeiro; Silva, Joao Santana da; Bezerra da Silva, Lea Assed; Kuga, Milton Carlos [UNESP]; Faria, Gisele [UNESP] (Elsevier B.V., 2014)
Introduction: The aim of this study was to characterize the response of mouse subcutaneous tissue to triple antibiotic paste (TAP) using conventional light microscopy and real-time PCR (qRT-PCR). Methods: Polyethylene tubes containing TAP or calcium hydroxide (CH) (ie, the control group) were implanted in mouse subcutaneous tissue. Animals that received empty tubes or no tubes were used as additional controls. After periods of 7, 21, and 63 days postimplantation, the specimens were removed and subjected to histologic processing. The number of inflammatory cells and vessels, vessel areas, vascular density, and relative percentage of collagen were evaluated. Gene expression of proinflammatory (interleukin-1 beta, tumor necrosis factor alpha, and interleukin 17) and anti-inflammatory (transforming growth factor beta) cytokines and angiogenic factors (vascular endothelial growth factor and hypoxia-inducible factor-1 alpha) was quantified by 7 and 21 days postimplantation. Results were analyzed using the Student t test, analysis of variance, and the Tukey test (alpha = 0.05). Results: TAP induced an exuberant inflammatory and angiogenic response, with higher numbers of inflammatory cells, higher vascular area and density, and lower relative percentage of collagen compared with CH. In general, the expression of genes involved in inflammation and angiogenesis was higher in the TAP group compared with animals that received CH or empty tubes. Conclusions: The response of mouse subcutaneous tissue to TAP was characterized by exuberant and persistent inflammatory and angiogenic responses with no repair and high gene expression of biomarkers associated with inflammation and angiogenesis.
Keywords: Biocompatibility; calcium hydroxide; intracanal dressing; triple antibiotic paste